2010
DOI: 10.1021/jp102186r
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Indirect Nuclear Spin−Spin Couplings in Isomers of Adenine: Novel Approach to Analyze Coupling Electron Deformation Density Using Localized Molecular Orbitals

Abstract: Adenine, an essential building block of nucleic acids present in all living systems, can occur in several tautomeric forms. The phenomenon of tautomerism can be investigated by several experimental methods, including nuclear magnetic resonance. In this study, long-range (1)H-(13)C and (1)H-(15)N coupling constants for N-alkyl derivatives related to four tautomers of adenine are investigated in DMSO and DMF solutions. To investigate the structural dependence of the coupling constants and to understand how polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…The basic framework topologies of the 3-, 7-, and 9-benzyladenine isomers (Scheme 1), determined by single-crystal X-ray diffraction analysis, were published previously. [25] The unit cell of 3-benzyladenine (1) contains four molecules, situated at the edges, with two benzyl groups pointing inside and two pointing outside of the cell. The four 7-benzyladenine (2) molecules have the same spatial arrangement, but there are four water molecules in the unit cell as well-this isomer crystallizes as a monohydrate.…”
Section: Single-crystal X-ray Diffractionmentioning
confidence: 99%
“…The basic framework topologies of the 3-, 7-, and 9-benzyladenine isomers (Scheme 1), determined by single-crystal X-ray diffraction analysis, were published previously. [25] The unit cell of 3-benzyladenine (1) contains four molecules, situated at the edges, with two benzyl groups pointing inside and two pointing outside of the cell. The four 7-benzyladenine (2) molecules have the same spatial arrangement, but there are four water molecules in the unit cell as well-this isomer crystallizes as a monohydrate.…”
Section: Single-crystal X-ray Diffractionmentioning
confidence: 99%
“…The majority of papers have identified this minor isomer to be N7-benzyladenine [10,11] while two groups identified this isomer as N3-benzyladenine [8,9]. It is commonly reported that the reaction of adenine with an alkyl halide at elevated temperatures in the presence of base yields the N9 and N7 regioisomers, whereas in the absence of base yields N3-alkylated adenine [13][14][15][16][17][18][19], and it has been reasoned that the formation of the N9/N7 regioisomers can be explained in terms of the dominance of the adenine tautomers, N9-H and N7-H [20]. Our aim was therefore to synthesize sufficient quantities of the minor benzyladenine regioisomer to allow for a full characterization by X-ray crystallography and two-dimensional NMR techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The 3‐subsituted adenine derivative, 3‐(butenyl)adeninium bromide ( 3 ), is somewhat more common, with structures of both neutral [3‐Et , CH 2 Ph , CH 2 C(H)CMe 2 , ribose ] and cationic [3‐Me, chloride or indole‐3‐acetate as counterion] structures previously reported. The asymmetric unit of 3 comprises a single molecule interacting with the bromide counterion via two hydrogen bonds (Fig.…”
Section: Resultsmentioning
confidence: 99%